2017
DOI: 10.18632/oncotarget.14471
|View full text |Cite|
|
Sign up to set email alerts
|

Th1high in tumor microenvironment is an indicator of poor prognosis for patients with NSCLC

Abstract: CD4+Th subsets play an important role in tumor progression but their expression characteristics and clinical significance in human tumor microenvironment remains unclear. In this study, we aim to analyze the expression and clinical significance of tissue-infiltrating Th1, Th2 and Th17 in lung cancer by flow cytometry. We found that the frequency of CD3+CD4+IFN-γ+Th1 in tumor nest was significantly lower than that in tumor boundary, adjacent normal lung tissue or corresponding lymph node tissue; the frequency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…While examining the possible pro-or anti-tumor roles of each TME cell type is beyond the scope of our holistic TME study, we found it interesting that the 32-cell feature sets consistently included both Th1 and Th2 cells. These two helper T cell subtypes were co-enriched in the same patient clusters, despite being thought to be associated with different processes; that is, Th1 cells induce IFNG expression and anti-tumor effects while Th2 release IL-4 and IL-10, which help allow for tumor-escape [46,47]. Whilst the less immunogenic and less favorably surviving LUAD patients showed elevated enrichment of both Th1 and Th2 cells, this result is in line with a previous study using different methods (e.g., flow cytometry) to show that high levels of Th1 in the TME is associated with worse prognosis in NSCLC [47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While examining the possible pro-or anti-tumor roles of each TME cell type is beyond the scope of our holistic TME study, we found it interesting that the 32-cell feature sets consistently included both Th1 and Th2 cells. These two helper T cell subtypes were co-enriched in the same patient clusters, despite being thought to be associated with different processes; that is, Th1 cells induce IFNG expression and anti-tumor effects while Th2 release IL-4 and IL-10, which help allow for tumor-escape [46,47]. Whilst the less immunogenic and less favorably surviving LUAD patients showed elevated enrichment of both Th1 and Th2 cells, this result is in line with a previous study using different methods (e.g., flow cytometry) to show that high levels of Th1 in the TME is associated with worse prognosis in NSCLC [47].…”
Section: Discussionmentioning
confidence: 99%
“…These two helper T cell subtypes were co-enriched in the same patient clusters, despite being thought to be associated with different processes; that is, Th1 cells induce IFNG expression and anti-tumor effects while Th2 release IL-4 and IL-10, which help allow for tumor-escape [46,47]. Whilst the less immunogenic and less favorably surviving LUAD patients showed elevated enrichment of both Th1 and Th2 cells, this result is in line with a previous study using different methods (e.g., flow cytometry) to show that high levels of Th1 in the TME is associated with worse prognosis in NSCLC [47]. Lastly, considering the relative scarcity of studies investigating the clinical differences between Th1 and Th2 cells in different TME contexts [48,49], it is possible that this Th1-Th2 balance could mark an avenue worthy of further prognostic investigation, either alone or while considering potential tumor promoting metabolic pathways previously mentioned.…”
Section: Discussionmentioning
confidence: 99%
“…Typically, the Th1 response is needed against tumors and viral infections. In the above-mentioned case, the T-cell-inactivating ligand PD-L1 on CD45+CD14+ monocytes/macrophages was more abundant in tumor tissue than in the adjacent nontumor tissues 138 . This observation can be reconciled with at least two possible scenarios.…”
Section: Intracellular and Extracellular Cancer Processesmentioning
confidence: 80%
“…In NSCLC specimens, discrete zones of Th2, Th17, and Th1 were found. These zones distinguished the tumor nest from the tumor boundary, adjacent normal lung tissue, or corresponding lymph node tissue 138 . IL-17 activates STAT3 and induces EMT in lung cancer cells in vitro .…”
Section: Intracellular and Extracellular Cancer Processesmentioning
confidence: 99%
“…Although most of the evidence supports that patients with more infiltrating Th1 cells exhibit a good prognosis, there is also research that indicates that patients with more infiltrating Th1 cells suffer a poorer prognosis compared with those with fewer Th1 cells, as evaluated by flow cytometry. The data from that study indicated that the IFN-γ secreted by Th1 cells could enhance the PD-L1 signal in macrophages and tumor cells [ 36 ]. Even though the Th1 and Th2 status was estimated from the bulk RNA sequencing indirectly, the information suggests that the roles of T helper cells in the tumor microenvironment are more complicated and merit further investigation.…”
Section: Discussionmentioning
confidence: 99%